Volatility spillovers of gold prices, oil prices, and economic policy uncertainty on the stock market of Pakistan. (18th June 2021) - Aziz, Tariq; Hussain, Afaque
The primary purpose of the study is to examine the spillover effect of the oil market, the gold market, and global economic policy uncertainty on the stock market in the context of Pakistan. The study uses time-series data for the period December 2010 to September 2019. To investigate the volatility spillovers, the study employed the exponential generalised autoregressive conditional heteroscedastic (EGARCH) model that allows for asymmetries. The results show that shocks in the gold market significantly transmit to the stock market returns. When the gold market is less volatile then the stock market shows higher volatility, vice versa. Further, the oil prices and global economic policy uncertainty have no significant volatility spillovers towards the stock market returns. The findings provide updated evidence about volatility transmissions from multiple factors to the stock market returns that are very important for investors and policymakers.